Continuous renal replacement therapy in neonates and children: what does the pediatrician need to know? An overview from the Critical Care Nephrology Section of the European Society of Paediatric and Neonatal Intensive Care (ESPNIC) - Gérard Cortina; Marco Daverio; Demet Demirkol; Rahul Chanchlani; Akash Deep (2023)
Continuous renal replacement therapy (CRRT) is the preferred method for renal support in critically ill and hemodynamically unstable children in the pediatric intensive care unit (PICU) as it allows for gentle removal of fluids and solutes. The most frequent indications for CRRT include acute kidney injury (AKI) and fluid overload (FO) as well as non-renal indications such as removal of toxic metabolites in acute liver failure, inborn errors of metabolism, and intoxications and removal of inflammatory mediators in sepsis. AKI and/or FO are common in critically ill children and their presence is associated with worse outcomes. Therefore, early recognition of AKI and FO is important and timely transfer of patients who might require CRRT to a center with institutional expertise should be considered. Although CRRT has been increasingly used in the critical care setting, due to the lack of standardized recommendations, wide practice variations exist regarding the main aspects of CRRT application in critically ill children. Conclusion: In this review, from the Critical Care Nephrology section of the European Society of Paediatric and Neonatal Intensive Care (ESPNIC), we summarize the key aspects of CRRT delivery and highlight the importance of adequate follow up among AKI survivors which might be of relevance for the general pediatric community. What is Known: • CRRT is the preferred method of renal support in critically ill and hemodynamically unstable children in the PICU as it allows for gentle removal of fluids and solutes. • Although CRRT has become an important and integral part of modern pediatric critical care, wide practice variations exist in all aspects of CRRT. What is New: • Given the lack of literature on guidance for a general pediatrician on when to refer a child for CRRT, we recommend timely transfer to a center with institutional expertise in CRRT, as both worsening AKI and FO have been associated with increased mortality. • Adequate follow-up of PICU patients with AKI and CRRT is highlighted as recent findings demonstrate that these children are at increased risk for adverse long-term outcomes.